A functional plastic and a method for producing the same

CN122898128APending Publication Date: 2026-10-13SHANGHAI BLOPAK NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611236766.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-12-31
Filing Date
2026-08-14
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

目前,用于尼龙6阻燃改性的稀土化合物主要包括三类:①稀土氧化物(如氧化铈、氧化镧),具有优异的自由基捕捉与抑烟性能,但与尼龙6相容性差,易团聚;②稀土次磷酸盐(如LaHP、CeHP),兼具磷系阻燃剂的气相阻燃作用与稀土的催化成炭作用,阻燃效率较高,但单独使用时气相阻燃效果不足,如CN118978134A公开了一种含稀土亚磷酸盐,通过将稀土亚磷酸盐与无机铝盐在水中反应,制备出具有提高尼龙阻燃性能的含稀土亚磷酸盐,并与二乙基次膦酸铝复配,形成具有良好阻燃效果的组合物,显著提高了尼龙的阻燃性能、流动性和冲击强度,增强了其在高温高湿环境下的稳定性,适用于航空航天和电子器件等领域;③稀土膦酸盐(如苯基膦酸镧、苯基膦酸铈),片层结构可提升分散性,但合成工艺复杂、成本高,且苯基结构在高温下易分解产生有毒气体

Benefits of technology

1.阻燃性能优异且环保:本发明核心稀土阻燃体系与协效阻燃体系双重协同,阻燃效率远高于单一阻燃体系,材料极限氧指数可达到32%以上,通过UL94 V-0级阻燃标准,且无卤、低烟、无有毒气体释放,符合环保要求,适用于食品、电子等高端包装领域。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of functional plastics and preparation method thereof, belong to plastic packaging material technical field.The functional plastics are made of 80-85% in-situ polymerization nylon 6, 6-9% lanthanum hypophosphite and nano cerium oxide compound core rare earth flame-retardant system, 7-10% tri (2-hydroxyethyl) isocyanurate and nano silicon dioxide compound synergistic flame-retardant system, 0.5-1% caprolactam-based silane polymerization modifier and 1-2% antioxidant and lubricant compound processing aid by mass percentage;Using in-situ polymerization, melt blending combined process, after raw material pretreatment, in-situ polymerization preparation rare earth-containing masterbatch, premixing, melt blending, forming processing and post-processing step preparation is obtained, constructs gas phase free radical quenching-coagulation phase carbon formation barrier-physical filling enhanced triple synergistic mechanism.The functional plastics are halogen-free, environmentally friendly, balanced mechanical properties, strong stability, suitable for the performance requirements of packaging scene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of plastic packaging materials technology, specifically to a functional plastic and its preparation method. The functional plastic is a highly dispersed rare earth flame-retardant plastic, suitable for high-end application scenarios with stringent requirements for flame retardant performance, mechanical properties and processing stability, such as high-end electronic components, precision instruments, and aerospace components. Background Technology

[0002] With the rapid development of industries such as electronics and information, precision manufacturing, aerospace, and healthcare, the global demand for high-end packaging materials continues to grow. Nylon 6 (PA6), as a high-performance engineering plastic, has become one of the core matrix materials for high-end packaging materials due to its excellent mechanical strength, impact resistance, barrier properties, and processability. However, Nylon 6 is inherently a flammable polymer with a limiting oxygen index (LOI) of only 25.6% and a vertical flammability rating of UL94 V-2. During combustion, it exhibits defects such as a high heat release rate, severe flaming dripping, and large smoke emission. These defects mean that pure Nylon 6 cannot meet the flame-retardant safety requirements of high-end packaging and must be modified with high-efficiency flame retardants to achieve its application.

[0003] Rare earth flame retardants, as an emerging field in halogen-free and environmentally friendly flame retardants, have attracted widespread attention due to their unique performance advantages. Rare earth elements (such as La, Ce, and Y) possess unique electronic structures, and their compounds play important roles in the flame retardant process: ① Catalytic char formation: Rare earth ions (such as La and Ce) can act as Lewis acid catalysts, promoting the cross-linking and dehydration of polymer molecular chains to form a dense char layer that blocks heat and oxygen; ② Free radical capture: Ce... 3+ / Ce 4+ Rare earth ions with variable valence states can be cyclically used to capture OH groups during combustion. -① Reactive free radicals such as H· can block the combustion chain reaction; ② Smoke suppression and detoxification: rare earth compounds can catalyze the oxidation of CO in flue gas to CO2, reducing the toxicity of flue gas. Currently, rare earth compounds used for flame retardant modification of nylon 6 mainly include three categories: ① Rare earth oxides (such as cerium oxide and lanthanum oxide), which have excellent free radical capture and smoke suppression properties, but have poor compatibility with nylon 6 and are prone to agglomeration; ② Rare earth hypophosphites (such as LaHP and CeHP), which combine the gas-phase flame retardant effect of phosphorus-based flame retardants with the catalytic char formation effect of rare earths, and have high flame retardant efficiency, but their gas-phase flame retardant effect is insufficient when used alone. For example, CN118978134A discloses a rare earth phosphite containing rare earth, which is modified by combining rare earth phosphite with non-reactive free radicals. Aluminum diethylphosphonate reacts in water to prepare rare earth-containing phosphites that improve the flame retardant properties of nylon. These phosphites are then compounded with aluminum diethylphosphonate to form a composition with excellent flame retardant effects, significantly improving the flame retardant properties, flowability, and impact strength of nylon, and enhancing its stability in high-temperature and high-humidity environments. This composition is suitable for aerospace and electronic devices. Rare earth phosphonates (such as lanthanum phenylphosphonate and cerium phenylphosphonate) have a layered structure that improves dispersibility, but their synthesis process is complex and costly, and the phenyl structure easily decomposes at high temperatures to produce toxic gases. Despite the significant advantages of rare earth flame retardant technology, existing rare earth-modified nylon 6 packaging materials still have the following problems: 1. The interfacial tension difference between rare earth flame retardants and the nylon 6 matrix is ​​huge, resulting in extremely poor compatibility. This causes rare earth particles to easily agglomerate during melt blending, forming micron-sized agglomerates, which limits the flame retardant efficiency and fails to meet the flame retardant requirements of high-end packaging. 2. The rare earth flame retardants and nylon 6 molecular chains are only physically mixed without chemical bonding; they are only bound by weak van der Waals forces. During processing such as melt blending and injection molding, rare earth particles are prone to secondary agglomeration due to shear force and temperature fluctuations, resulting in large fluctuations in the performance of finished products, which cannot meet the stringent requirements of high-end packaging for performance consistency; 3. Existing technologies mostly use a single synergist (such as ammonium polyphosphate or aluminum diethylphosphonate) in combination with rare earth flame retardants, but the synergistic mechanism between synergists and rare earths is unreasonable and cannot form a stable synergistic flame retardant.

[0004] To address the aforementioned issues, existing technologies have made some attempts, such as using silane coupling agents (e.g., KH-550, KH-560) to surface-treat rare earth particles in an attempt to improve compatibility. However, the modified rare earth particles are still physically dispersed, and the binding of the coupling agent to the rare earth particles is a physical adsorption, which is prone to desorption during high-temperature processing, resulting in insufficient dispersion stability. Adding fillers such as nano-montmorillonite and nano-hydroxyapatite attempts to inhibit agglomeration through physical barriers. For example, CN120248436A discloses a composite flame retardant made from the following raw materials in parts by weight: 30-60 parts by weight of an organophosphorus chelating agent, 10-25 parts by weight of a soluble rare earth inorganic salt, and 150-200 parts by weight of zeolite. These materials self-assemble on the zeolite surface through electrostatic interaction to form a complex, which is uniformly dispersed in ABS resin. When used in conjunction with a small amount of flame retardant synergist, it improves flame retardancy, smoke suppression, and mechanical properties. CN120904679A discloses a high-performance polyamide flame-retardant composite material based on elemental synergy. The preparation method includes steps such as preparing a phosphorus-nitrogen flame retardant, preparing a surface-modified rare-earth-silicon-based material, preparing a mixture, and extrusion granulation. The step of preparing the mixture involves uniformly mixing brominated polystyrene (BPS), the phosphorus-nitrogen flame retardant, the rare-earth-silicon-based material, glass fiber, antioxidant 1098, the heat stabilizer phenyl diisooctyl phosphite, nylon 66, and nylon 6 to obtain a mixture. Synergistic modification with bromine, phosphorus, nitrogen, silicon, and rare-earth elements is employed. By preparing the phosphorus-nitrogen flame retardant and the surface-modified rare-earth-silicon-based material, combined with glass fiber, antioxidant, and heat stabilizer, a multi-element synergistic effect is formed, improving flame-retardant efficiency and mechanical properties. However, this type of filler has similar surface properties to the rare-earth flame retardant and is prone to forming composite agglomerates, which actually reduces the flame-retardant efficiency.

[0005] Therefore, given the shortcomings of existing technologies, such as rare earth agglomeration, poor dispersibility, lack of chemical bonding between rare earth and nylon 6 molecular chains, insufficient processing stability, poor synergy between the synergistic system and rare earth, and low flame retardant efficiency caused by traditional melt blending, it is necessary to address the fundamental defects of existing technologies from the source and provide a functional plastic with balanced performance, stable processing, and environmental safety, as well as its preparation method, to achieve in-situ dispersion and stabilization of rare earth flame retardants. Summary of the Invention

[0006] To address the aforementioned problems and deficiencies, this invention provides a functional plastic, comprising, by weight percentage, the following components: 80-85% plastic matrix, 6-9% core rare earth flame retardant system, 7-10% synergistic flame retardant system, 0.5-1% polymerization modifier, and 1-2% processing aid; the plastic matrix is ​​in-situ polymerized nylon 6, the core rare earth flame retardant system is composed of lanthanum hypophosphite (LaHP) and nano-cerium oxide (CeO2), and the synergistic flame retardant system is composed of tris(2-hydroxyethyl) isocyanurate and nano-silica; the polymer... The modifier is caprolactam-based silane (HLS), and the processing aid consists of antioxidants and lubricants. Through a combined process of in-situ polymerization and melt blending, and with the dual locking of caprolactam-based silane through "amino coordination + silicon-based bonding," and further combined with the synergistic system of tris(2-hydroxyethyl) isocyanurate and nano-silica, a relatively complete triple synergistic flame retardant mechanism is constructed, which includes gas-phase free radical quenching, condensed phase char formation barrier, and physical filling reinforcement. At the same time, the rare earth dispersion particle size of this functional plastic is ≤300nm, LOI≥37.5%, UL94 V-0 rating, tensile strength≥50MPa, and processing qualification rate≥98%. It solves the pain points of traditional rare earth modified nylon 6 such as agglomeration, poor stability, and low flame retardant efficiency. The components of this functional plastic work together to ensure excellent flame retardant performance while taking into account the material's processing performance and mechanical stability. It is suitable for packaging scenarios with stringent performance requirements, such as high-end electronic components, precision instruments, and aerospace components, and has a good market prospect.

[0007] Specifically, one aspect of this invention provides a functional plastic, which, by weight percentage, is composed of the following components: Plastic matrix 80-85%, core rare earth flame retardant system 6-9%, synergistic flame retardant system 7-10%, polymerization modifier 0.5-1%, processing aid 1-2%; The plastic matrix is ​​in-situ polymerized nylon 6. The core rare earth flame retardant system is composed of lanthanum hypophosphite (LaHP) and nano-cerium oxide (CeO2) in a mass ratio of 3:1, wherein the nano-cerium oxide has a particle size of 2-50 nm. The synergistic flame retardant system is composed of tris(2-hydroxyethyl) isocyanurate and nano-silica in a mass ratio of 3:1. The polymerization modifier is caprolactam silane (HLS). The processing aid is composed of antioxidant and lubricant in a mass ratio of 1:1. The antioxidant is antioxidant 1010 or antioxidant 1076, and the lubricant is calcium stearate or pentaerythritol stearate (PETS).

[0008] The plastic matrix is ​​made of in-situ polymerized nylon 6, which features high crystallinity, excellent mechanical strength, and strong chemical corrosion resistance. The in-situ polymerization process allows for more uniform dispersion of subsequent flame-retardant components and modifiers within the matrix, avoiding the component agglomeration problems caused by conventional blending. The core flame-retardant system uses lanthanum hypophosphite (LaHP) and nano-cerium oxide (CeO2) in a 3:1 mass ratio to form a rare-earth-based high-efficiency flame-retardant system. Unlike traditional halogen flame retardants, it offers advantages such as halogen-free environmental friendliness and low smoke density. Lanthanum hypophosphite, as the main flame-retardant component, decomposes during combustion to produce phosphoric acid, forming a dense char layer on the material surface that blocks oxygen and heat transfer. Nano-cerium oxide, as a synergistic component, catalyzes the decomposition reaction of lanthanum hypophosphite, improving flame-retardant efficiency. Furthermore, its rare-earth ion properties inhibit the chain reaction of free radicals during combustion, reducing smoke production. The synergistic flame retardant system consists of tris(2-hydroxyethyl) isocyanurate and nano-silica in a 3:1 mass ratio, forming a dual synergistic effect with the core rare-earth flame retardant system. The hydroxyl and isocyanurate groups in tris(2-hydroxyethyl) isocyanurate can undergo a cross-linking reaction with the decomposition products of lanthanum hypophosphite during combustion, further enhancing the density and stability of the char layer. Nano-silica, as an inorganic flame retardant synergist, can fill the pores of the char layer, improving its heat insulation and oxygen barrier properties, while also enhancing the material's hardness and wear resistance. The polymerization modifier is caprolactam-based silane (HLS), whose caprolactam groups can copolymerize with the molecular chains of nylon 6, while the silane groups can form cross-linking points between components. This improves the compatibility of the flame retardant components with the plastic matrix, preventing the flame retardant from migrating and precipitating during processing and use, and also enhances the material's mechanical properties and aging resistance. The processing aid consists of an antioxidant and a lubricant in a 1:1 mass ratio, used to improve the material's processing stability and molding flowability. Antioxidants 1010 or 1076 are selected to inhibit oxidative degradation of the material during high-temperature processing (such as melt blending and injection molding), preventing yellowing and degradation of mechanical properties. Calcium stearate or pentaerythritol stearate (PETS) is selected as the lubricant to reduce friction between components and between components and processing equipment, improve the fluidity of the molten material, enhance the surface finish of the molded material, and prevent localized overheating degradation caused by frictional heat during processing. The nano-cerium oxide particles have a size of 2-50 nm. Particles that are too small are prone to agglomeration, reducing dispersion uniformity; particles that are too large cannot fully utilize the catalytic synergistic effect of the nanoparticles. This particle size range ensures uniform dispersion in the matrix, maximizing the synergistic flame-retardant effect.

[0009] Furthermore, the mass percentages of each component are as follows: in-situ polymerized nylon 6 82%, lanthanum hypophosphite 6%, nano-cerium oxide 2%, tris(2-hydroxyethyl) isocyanurate 6%, nano-silica 2%, caprolactam silane 0.8%, antioxidant 1010 0.6%, and calcium stearate 0.6%.

[0010] Furthermore, the viscosity-average molecular weight of the in-situ polymerized nylon 6 is 3.0 × 10⁻⁶. 4 -5×10 5 The molecular chain contains 0.3-0.5% siloxane groups (i.e., 3-5 siloxane structural groups per 1000 chain segments). This molecular weight range can balance the processing fluidity of the material with the structural strength after molding: molecular weight below 3.0 × 10⁻⁶. 4 When the material's mechanical properties are insufficient, it is prone to brittle fracture; when the molecular weight is higher than 5×10 5 When the melt viscosity is too high, it increases the difficulty of processing such as extrusion and injection molding.

[0011] Furthermore, the caprolactam silane has a molecular weight of 200-300 g / mol and an amino content of 0.8-1.5 mmol / g. This range ensures that it has suitable reactivity during in-situ polymerization. If the molecular weight is too high, its dispersibility will be reduced, and if the amino content is too low, the crosslinking modification effect cannot be fully exerted.

[0012] Furthermore, the nano-silica is surface-modified with silane coupling agent KH-560, with the amount of modifier being 3-5% of the mass of the nano-silica. The epoxy groups of KH-560 can react with the hydroxyl groups on the surface of the nano-silica, while the organic groups at the other end can interact with the nylon matrix and other components, effectively improving the compatibility between the nano-silica and the organic matrix, solving the problem of nano-silica agglomeration, and enhancing the interfacial bonding and processing stability of the material.

[0013] Furthermore, the plastic matrix can also be an in-situ polymerized blend of nylon 6 and polyamide 66 at a mass ratio of 9:1. The addition of polyamide 66 can slightly improve the heat resistance and creep resistance of the material, and it has good compatibility with nylon 6. The 9:1 ratio can avoid the problems of excessively fast crystallization rate and increased internal stress during molding caused by excessive polyamide 66 content.

[0014] Another aspect of the present invention provides a method for preparing functional plastics, comprising the following steps: (1) Raw material pretreatment: Vacuum dry caprolactam monomer at 100-110℃ for 3-4 hours, and control the moisture content (free moisture content) below 0.05%. As it is a polymer monomer, excessive moisture content will affect the rate and molecular weight distribution of in-situ polymerization reaction. Drying removes excess adsorbed water and free water from the caprolactam monomer raw material, making the initial moisture content stable and controllable, and avoiding excessive moisture leading to uncontrolled polymerization rate, excessively wide molecular weight distribution, and decreased product performance. Lanthanum hypophosphite, nano-cerium oxide, tris(2-hydroxyethyl) isocyanurate, and nano-silica are vacuum dried at 85-90℃ for 6-8 hours, and the moisture content is controlled below 0.2%, to remove surface free adsorbed water and avoid introducing excessive moisture. Long-term low-temperature drying of the above materials can avoid component decomposition. Caprolactam-based silane and processing aids are dried at 80℃ for 2-3 hours to remove surface adsorbed water. Since the heat resistance of this material is relatively poor, low-temperature drying can prevent the modifier from failing and the aid from decomposing. The above treatment can prevent moisture from causing side reactions (such as excessive hydrolysis) and generating bubbles during subsequent high-temperature polymerization and melting processes, thus affecting material properties and molding quality.

[0015] (2) Preparation of rare earth-containing masterbatch by in-situ polymerization: Weigh the pretreated caprolactam monomer, caprolactam silane, lanthanum hypophosphite, and nano-cerium oxide according to the mass percentage, add them to the polymerization reactor, and then add 0.02%-0.5% of deionized water as a polymerization initiator to the reactor; after purging the reactor with nitrogen to replace the air in the reactor 3 times, maintain continuous nitrogen protection, start stirring and heat to 145-155℃ at a rate of 3-5℃ / min, stirring at a rate of 300-400r / min, and maintain the temperature for 4-5 hours for polymerization; after polymerization is completed, stop heating, continue stirring and cool to room temperature, discharge and granulate to obtain rare earth-containing in-situ polymerized nylon 6 masterbatch. This step uses low-temperature hydrolysis ring-opening polymerization initiated by trace amounts of water and catalyzed by lanthanum hypophosphite, which is different from traditional non-catalyzed high-temperature hydrolysis polymerization. Its reaction logic is as follows: ①Initiation stage: The added trace amount of deionized water acts as a ring-opening initiator, reacting with caprolactam to generate aminocaproic acid active species, initiating the chain growth reaction; the amino group of caprolactam silane can serve as an auxiliary initiation site, increasing the number of active centers and synergistically enhancing the polymerization initiation rate; the siloxane group of caprolactam silane undergoes partial hydrolysis under the action of trace amount of water in the system, and the generated silanol groups participate in subsequent interfacial bonding reactions, with extremely low water consumption, which does not affect the water requirement for polymerization initiation.

[0016] ② Catalytic growth stage: La dissociates from lanthanum hypophosphite 3+As a Lewis acid catalyst, it coordinates with the carbonyl oxygen of caprolactam, weakening the amide bond energy and significantly reducing the activation energy of the ring-opening reaction. This allows the polymerization reaction to proceed stably under mild conditions of 145-155℃, eliminating the need for the high temperatures of traditional hydrolysis polymerization (above 250℃). High molecular weight polymer products can be obtained in 4-5 hours.

[0017] ③ In-situ dispersion modification stage: As polymerization proceeds, caprolactam silane is incorporated into the main chain of nylon 6 molecules through active groups, introducing siloxane groups into the molecular structure and achieving in-situ modification of the molecular chain; rare earth flame retardant particles are uniformly encapsulated during the gradual growth of the molecular chain, achieving nanoscale in-situ dispersion and avoiding the agglomeration problem of conventional blending processes from the source.

[0018] (3) Premixing: Weigh out the rare earth-containing in-situ polymerized nylon 6 masterbatch, tris(2-hydroxyethyl) isocyanurate, nano silica and processing aids by mass percentage, add them to a high-speed mixer, mix at 1300-1600 r / min for 8-12 minutes, and control the mixing temperature at 35-45℃ to obtain a uniform premix. This step aims to quickly and uniformly mix the rare earth-containing masterbatch with the synergistic flame retardant system and processing aids, laying the foundation for subsequent melt blending. The high-speed mixer speed of 1300-1600 r / min can generate strong shear force, break up component agglomeration, and improve mixing uniformity. The mixing temperature of 35-45℃ is lower to avoid the volatilization of the additives, and at the same time, the shear heat generation slightly activates the surface of the components, enhancing the compatibility of the mixture. The mixing time of 8-12 minutes ensures that each component is uniformly dispersed and there is no local enrichment.

[0019] (4) Melt blending: The premixed material is fed into a twin-screw extruder, melt blended and extruded, cooled in a water tank and air-dried, and then pelletized by a pelletizer to obtain flame retardant masterbatch; the melt blending process, through the shearing and mixing action of the twin-screw extruder, allows the components to fully combine in the molten state to form a homogeneous system.

[0020] (5) Molding and processing: The flame retardant masterbatch is vacuum dried at 110-120℃ for 3-4 hours to further remove the moisture adsorbed during storage, and then put into a micro injection molding machine for injection molding to obtain the finished plastic packaging material. (6) Post-treatment: The molded finished product is kept at 80-85℃ for 2-3 hours to eliminate internal stress and prevent deformation and cracking caused by stress release during use. At the same time, the crystal structure of the material can be further optimized to improve mechanical properties and dimensional stability.

[0021] This preparation method employs a step-by-step process of "in-situ polymerization - premixing - melt blending - molding and processing - post-treatment." The in-situ polymerization stage achieves "molecular-level dispersion" of the rare earth flame retardant, while the melt blending stage optimizes the uniform distribution of the synergistic system, avoiding the defects of a single process. By precisely controlling the parameters of each step, uniform dispersion of components and sufficient reaction are ensured, thereby improving the overall performance of the material.

[0022] Furthermore, in step (2), the stirring rate of the polymerization reactor is 350 r / min, the polymerization temperature is 150℃, the holding time is 4.5 hours, and the nitrogen gas introduction rate is 0.5-1 L / min; in step (4), the length-to-diameter ratio of the twin-screw extruder is 40:1, which can provide sufficient shearing time and mixing space to ensure uniform dispersion of components.

[0023] Furthermore, in step (4), the temperature of each section of the twin-screw extruder is set as follows: Zone I (material preheating zone) 180-190℃, Zone II (preliminary melting zone) 200-210℃, Zone III (complete melting zone) 220-230℃, Zone IV (deep mixing zone) 235-245℃, Zone V (stabilization zone) 230-240℃, and the die head (forming zone) temperature is 235-245℃. This temperature gradient setting can avoid local overheating and degradation of the material, while ensuring sufficient melting. The screw speed is 250-280r / min, and the feeding speed is 17-20r / min. The matching of the two can control the residence time of the material in the barrel, ensuring the mixing effect and production efficiency.

[0024] In step (5), the temperatures of each section of the injection molding machine are set as follows: Zone I 220-230℃, Zone II 230-240℃, Zone III 240-250℃, Zone IV 245-255℃, and the die head temperature is 240-250℃; the injection pressure is 80-100MPa, the holding pressure is 50-70MPa, the holding time is 12-20 seconds, the cooling time is 25-35 seconds, and the mold temperature is 45-60℃. The temperature range of the injection molding machine is connected with that of the twin-screw extruder to avoid degradation caused by secondary heating of the material; the injection pressure of 80-100MPa can ensure that the material fills the mold cavity, the holding pressure of 50-70MPa can prevent the molded parts from shrinking, the holding time is 12-20 seconds, the cooling time is 25-35 seconds, and the mold temperature is 45-60℃. The optimization of the mold temperature and cooling time can reduce the internal stress of molding and improve the dimensional accuracy and mechanical properties of the finished product.

[0025] Furthermore, in step (5), the temperature of the injection mold is 50°C and the cooling time is 30 seconds.

[0026] The beneficial effects of this invention include: 1. Excellent flame retardant performance and environmentally friendly: The core rare earth flame retardant system and the synergistic flame retardant system of this invention work together to achieve a flame retardant efficiency far higher than that of a single flame retardant system. The limiting oxygen index of the material can reach more than 32%, which meets the UL94 V-0 flame retardant standard. It is also halogen-free, low-smoke, and releases no toxic gases, meeting environmental protection requirements and suitable for high-end packaging fields such as food and electronics.

[0027] 2. Balanced mechanical properties: The synergistic effect of in-situ polymerization and modifiers solves the problem of decreased material mechanical properties caused by the addition of flame retardants. The finished product has a tensile strength ≥50MPa and an impact strength ≥5.5kJ / m. 2 It also possesses good wear resistance and chemical corrosion resistance, meeting the structural strength requirements of packaging materials.

[0028] 3. High stability: Through processes such as raw material pretreatment, nitrogen protection, and temperature gradient control, combined with the action of antioxidants, the oxidative degradation during material processing and use is effectively inhibited. At the same time, the flame retardant components have good compatibility with the matrix and no migration or precipitation. Combined with the step-by-step preparation process, the material has excellent melt flowability, which can be smoothly realized in extrusion, injection molding and other molding processes. The finished product has a smooth surface, high dimensional accuracy, and no defects such as bubbles and cracks. The material has stable performance in long-term use. Detailed Implementation

[0029] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] It will be understood by those skilled in the art that, unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. It should also be understood that terms such as those defined in general dictionaries should be understood to have the meaning consistent with their meaning in the context of the prior art, and should not be interpreted in an idealized or overly formal sense unless specifically defined as herein. The reagents used herein may be commercially available related products, and performance testing standards refer to industry or national standards.

[0031] Those skilled in the art will understand that, unless specifically stated otherwise, the singular forms “a,” “an,” “the,” and “the” used herein may also include the plural forms. It should be further understood that the term “comprising” as used in this specification means the presence of the stated features, integers, steps, operations, elements, and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups thereof. The term “and / or” as used herein includes all or any units and all combinations of one or more associated listed items.

[0032] The performance tests in the embodiments and comparative examples of this invention adopt the following test standards: Limiting Oxygen Index (LOI) GB / T 2406.2-2009; Vertical Burning Rating (3.2mm) GB / T 2408-2021; Tensile Strength and Elongation at Break GB / T 1040.2-2006; Notched Impact Strength GB / T 1843-2008; Peak Heat Release Rate (PHRR) and Total Smoke Release (TSR) ISO5660-1:2015; Flame Retardant Migration GB 4806.7-2023; Tensile Strength Retention Rate after Thermo-Oxidative Aging (150℃, 500h) GB / T 7141-2015.

[0033] Example 1 A functional plastic was prepared by the following method: (1) Raw material pretreatment: caprolactam monomer was placed in a vacuum drying oven and dried at 105°C and a vacuum of -0.085MPa for 3.5 hours. The moisture content was 0.04% by Karl Fischer method. Lanthanum hypophosphite (purity 99.2%), nano-cerium oxide (particle size 20nm, purity 99.5%), tris(2-hydroxyethyl) isocyanurate (purity 98.5%), and nano-silica (particle size 60nm, after 4wt) The silane coupling agent (KH-560 modified) was dried at 88℃ and vacuum degree -0.085MPa for 7 hours, and the moisture content was 0.15%. Caprolactam silane (molecular formula: N-(2-caprolactam ethyl)triethoxysilane, molecular weight 250g / mol, amino content 1.0mmol / g), antioxidant 1010 (purity 99.5%), and calcium stearate (purity 99%) were dried at 80℃ for 2.5 hours to completely remove surface adsorbed water. (2) Preparation of rare earth-containing masterbatch by in-situ polymerization: Weigh 820g of caprolactam, 8g of caprolactam-silane, 60g of lanthanum hypophosphite, and 20g of nano-cerium oxide, add them to a 5L polymerization reactor, and then accurately add 0.164g of deionized water (accounting for 0.02% of the mass of caprolactam monomer) as a polymerization initiator. Replace with nitrogen three times (1L / min each time, for 5 minutes); start stirring at 350r / min, heat to 150℃ at 5℃ / min, and maintain the temperature for 4.5 hours, with a nitrogen gas introduction rate of 0.8L / min; after cooling to room temperature, granulate to obtain rare earth-containing masterbatch with a particle size of 2.5mm. The viscosity-average molecular weight of the in-situ polymerized nylon 6 was measured to be 3.0×10⁻⁶. 4 (3) Premixing: Weigh 908g of rare earth masterbatch, 60g of tris(2-hydroxyethyl) isocyanurate, 20g of nano silica, 6g of antioxidant 1010, and 6g of calcium stearate, add them to a 10L high-speed mixer, mix at 1500r / min and 40℃ for 10 minutes until uniform. (4) Melt blending: Feed the premixed material into a twin-screw extruder (length to diameter ratio 40:1), set the temperature of each section as follows: Zone I 185℃, Zone II 205℃, Zone III 225℃, Zone IV 240℃, Zone V 235℃, and die head 240℃; screw speed 265r / min, feeding speed 18r / min; after extrusion, cool in a 28℃ water bath, air dry, and pelletize to obtain flame retardant masterbatch. (5) Molding process: The flame retardant masterbatch was dried at 115℃ and vacuum degree -0.085MPa for 3.5 hours, with a moisture content of 0.09%; it was put into a micro injection molding machine with the following temperature zones: Zone I 225℃, Zone II 235℃, Zone III 245℃, Zone IV 250℃, and the die head 245℃; the mold temperature was 50℃, the injection pressure was 90MPa, the holding pressure was 60MPa, the holding time was 15 seconds, and the cooling time was 30 seconds. A standard sample of 3.2mm was obtained by injection molding. (6) Post-treatment: The sample was treated at 82℃ for 2.5 hours and then allowed to cool naturally to eliminate internal stress.

[0034] The product was tested, and the results showed that the limiting oxygen index (LOI) of the functional plastic in this embodiment was 37.8%; the vertical flammability rating reached UL94 V-0 (3.2mm specimen), with a flameless burning time of 3 seconds and no flaming dripping; the tensile strength was 50.8MPa, the elongation at break was 10.2%; and the notched impact strength was 5.7kJ / m. 2 The peak heat release rate (PHRR) is 345.2 kW / m³. 2 Total smoke emissions (TSR) were 2290.6 m³. 2 / m 2 TEM testing showed that the rare earth particle size was 275 nm and the agglomerate ratio was 0.7%; the qualified rate of 1000 finished products was 98.6%; the flame retardant migration was 0.006 mg / kg; after 500 hours of heat aging at 150℃, the tensile strength retention rate was 92.5%, and all properties showed high dispersibility, high flame retardancy and excellent stability.

[0035] Example 2 A functional plastic was prepared using the method described in Example 1, differing from Example 1 only in that the amount of caprolactam-silane added was 5g, caprolactam 823g, and the polymerization initiator was 4.115g of deionized water (0.5% of the caprolactam monomer mass). The viscosity-average molecular weight of the in-situ polymerized nylon 6 was measured to be 1.7 × 10⁻⁶. 5 .

[0036] The product was tested, and the results showed that the limiting oxygen index (LOI) of the functional plastic in this embodiment was 37.2%; the vertical flammability rating reached UL94 V-0 (3.2mm specimen), with a flameless burning time of 5 seconds and no flaming dripping; the tensile strength was 50.1MPa, the elongation at break was 9.9%; and the notched impact strength was 5.4kJ / m. 2 The peak heat release rate (PHRR) is 352.7 kW / m³. 2 TEM testing showed that the rare earth particle size was 290 nm, and the agglomerate ratio was 1.2%. The processing qualification rate of 1000 finished products was 98.2%. After 500 hours of heat aging at 150℃, the tensile strength retention rate was 91.3%. Although the double locking effect was slightly weakened due to the reduced amount of caprolactam silane added, and the dispersibility and flame retardant efficiency decreased slightly, all properties still met the usage requirements. Example 3 A functional plastic was prepared by the following method: (1) Raw material pretreatment: caprolactam monomer was placed in a vacuum drying oven and dried at 100°C and a vacuum of -0.085MPa for 3 hours. The moisture content was 0.037% by Karl Fischer method. Lanthanum hypophosphite (purity 99.2%), nano-cerium oxide (particle size 20-50nm, purity 99.5%), tris(2-hydroxyethyl) isocyanurate (purity 98.5%), and nano-silica (particle size 60nm, dried at 3000W) were also prepared. t% of silane coupling agent KH-560 modified was dried at 85℃ and vacuum degree -0.085MPa for 8 hours, and the moisture content was 0.10%; caprolactam silane (molecular formula: N-[5-(trimethoxysilylpropyl)-2-aza-1-oxopentyl]caprolactam, amino content 1.5mmol / g), antioxidant 1010 (purity 99.5%), and calcium stearate (purity 99%) were dried at 80℃ for 3 hours to completely remove surface adsorbed water. (2) Preparation of rare earth-containing masterbatch by in-situ polymerization: Weigh 830g of caprolactam, 8g of caprolactam-silane, 60g of lanthanum hypophosphite, and 20g of nano-cerium oxide, add them to a 5L polymerization reactor, and then accurately add 0.83g of deionized water (0.1% of the mass of caprolactam monomer) as a polymerization initiator. Replace with nitrogen three times (0.8L / min each time, for 5 minutes); start stirring at 300r / min, heat to 145℃ at 5℃ / min, and maintain the temperature for 5 hours, with nitrogen gas introduced at a rate of 1L / min; after cooling to room temperature, pelletize to obtain rare earth-containing masterbatch with a particle size of 2.3mm. The viscosity-average molecular weight of the in-situ polymerized nylon 6 was measured to be 3.4×10⁻⁶. 4 (3) Premixing: Weigh 918g of rare earth masterbatch, 52.5g of tris(2-hydroxyethyl) isocyanurate, 17.5g of nano silica, 6g of antioxidant 1010, and 6g of calcium stearate, add them to a 10L high-speed mixer, mix at 1300r / min and 45℃ for 8 minutes until uniform. (4) Melt blending: Feed the premixed material into a twin-screw extruder (length-to-diameter ratio 40:1), set the temperature of each section as follows: Zone I 180℃, Zone II 200℃, Zone III 220℃, Zone IV 235℃, Zone V 230℃, and die head 235℃; screw speed 250r / min, feeding speed 17r / min; after extrusion, cool in a 25℃ water bath, air dry, and pelletize to obtain flame retardant masterbatch. (5) Molding process: The flame retardant masterbatch was dried at 110℃ and vacuum degree -0.085MPa for 4 hours, with a moisture content of 0.08%; it was put into a micro injection molding machine with the following temperature zones: Zone I 220℃, Zone II 230℃, Zone III 240℃, Zone IV 245℃, and the die head 240℃; the mold temperature was 45℃, the injection pressure was 80MPa, the holding pressure was 50MPa, the holding time was 12 seconds, and the cooling time was 25 seconds. A standard sample of 3.2mm was obtained by injection molding. (6) Post-treatment: The sample was kept at 80℃ for 3 hours and then naturally cooled to eliminate internal stress.

[0037] The product was tested, and the results showed that the limiting oxygen index (LOI) of the functional plastic in this embodiment was 37.5%; the vertical flammability rating reached UL94 V-0 (3.2mm specimen), with a flameless burning time of 4 seconds and no flaming dripping; the tensile strength was 50.5MPa, the elongation at break was 10%; and the notched impact strength was 5.5kJ / m. 2 The peak heat release rate (PHRR) is 349.5 kW / m³. 2 TEM testing showed that the rare earth particles were dispersed at a size of 280 nm, with agglomerates accounting for 0.9%; the pass rate of 1000 finished products was 98.4%; after 500 hours of heat aging at 150℃, the tensile strength retention rate was 92.3%, and all properties demonstrated high dispersibility, high flame retardancy and excellent stability.

[0038] Example 4 A functional plastic was prepared by the following method: (1) Raw material pretreatment: caprolactam monomer, adipic acid, and hexamethylenediamine were placed in a vacuum drying oven and dried at 110°C and a vacuum of -0.085MPa for 4 hours. The moisture content was 0.031% as determined by Karl Fischer method. Lanthanum hypophosphite (purity 99.2%), nano-cerium oxide (particle size 2-25nm, purity 99.5%), tris(2-hydroxyethyl) isocyanurate (purity 98.5%), and nano-silica (particle size 60nm) were also prepared. nm, modified with 5wt% silane coupling agent KH-560, was dried at 90℃ and vacuum degree -0.085MPa for 6 hours, with a moisture content of 0.07%; caprolactam silane (molecular formula: N-(2-caprolactam ethyl)triethoxysilane, molecular weight 250g / mol, amino content 0.8mmol / g), antioxidant 1010 (purity 99.5%), and calcium stearate (purity 99%) were dried at 80℃ for 2 hours to completely remove surface adsorbed water. (2) Preparation of rare earth-containing masterbatch by in-situ polymerization: Nylon 66 was obtained by polymerizing adipic acid and hexamethylenediamine. 738g of caprolactam, 82g of nylon 66, 8g of caprolactam-based silane, 60g of lanthanum hypophosphite, and 20g of nano-cerium oxide were weighed and added to a 5L polymerization reactor. Then, 0.369g of deionized water (accounting for 0.05% of the mass of caprolactam monomer) was accurately added as a polymerization initiator. Nitrogen gas was purged three times (1.5L / min each time, for 5 minutes). Stirring was started at 400r / min, and the temperature was increased to 155℃ at 5℃ / min. The temperature was maintained for 4 hours, and the nitrogen gas was introduced at a rate of 0.5L / min. After cooling to room temperature, the mixture was pelletized to obtain rare earth-containing masterbatch with a particle size of 2.2mm. The viscosity-average molecular weight of the in-situ polymerized nylon 6 / nylon 66 blend was measured to be 4.5×10⁻⁶. 5(3) Premixing: Weigh 908g of rare earth masterbatch, 60g of tris(2-hydroxyethyl) isocyanurate, 20g of nano silica, 6g of antioxidant 1010, and 6g of calcium stearate, add them to a 10L high-speed mixer, mix at 1600r / min and 35℃ for 12 minutes until uniform. (4) Melt blending: Feed the premixed material into a twin-screw extruder (length-to-diameter ratio 40:1), set the temperature of each section as follows: Zone I 190℃, Zone II 210℃, Zone III 230℃, Zone IV 245℃, Zone V 240℃, and die head 245℃; screw speed 280r / min, feeding speed 20r / min; after extrusion, cool in a 23℃ water bath, air dry, and pelletize to obtain flame retardant masterbatch. (5) Molding process: The flame retardant masterbatch was dried at 120℃ and vacuum degree -0.085MPa for 3 hours, with a moisture content of 0.06%; it was put into a micro injection molding machine with the following temperature zones: Zone I 230℃, Zone II 240℃, Zone III 250℃, Zone IV 255℃, and the die head 250℃; the mold temperature was 60℃, the injection pressure was 100MPa, the holding pressure was 70MPa, the holding time was 20 seconds, and the cooling time was 35 seconds. A standard sample of 3.2mm was obtained by injection molding. (6) Post-treatment: The sample was kept at 85℃ for 3 hours and then allowed to cool naturally to eliminate internal stress.

[0039] The product was tested, and the results showed that the limiting oxygen index (LOI) of the functional plastic in this embodiment was 38.2%; the vertical flammability rating reached UL94 V-0 (3.2mm specimen), with a flameless burning time of 2 seconds and no flaming dripping; the tensile strength was 52.3MPa, the elongation at break was 10.1%; and the notched impact strength was 5.6kJ / m. 2 The peak heat release rate (PHRR) is 342.8 kW / m³. 2 TEM testing showed that the rare earth particle size was 262 nm, and the agglomerate ratio was 0.42%. The qualified rate of 1000 finished products was 98.8%. After 500 hours of heat aging at 150℃, the tensile strength retention rate was 94.7%. All properties showed high dispersibility, high flame retardancy and excellent stability. It can be seen that the addition of nylon 66 further promoted the char formation reaction, which slightly improved the flame retardant performance and mechanical strength.

[0040] Example 5 A functional plastic was prepared using the method described in Example 1, the only difference being that the processing aids used were 6g of antioxidant 1076 (99.5% purity) and 6g of lubricant pentaerythritol stearate (PETS, 99.0% purity).

[0041] The product was tested, and the results showed that the limiting oxygen index (LOI) of the functional plastic in this embodiment was 37.7%; the vertical flammability rating was UL94 V-0 (3.2mm sample), with a flameless burning time of 3 seconds and no flaming dripping; the tensile strength was 50.6MPa, the elongation at break was 10.3%; and the notched impact strength was 5.8kJ / m. 2 The melt flow rate (230℃ / 2.16kg) is 11.3g / 10min; the peak heat release rate (PHRR) is 344.6kW / m³. 2 TEM testing showed that the rare earth particle size was 278 nm, with agglomerates accounting for 0.8%; the pass rate of 1000 finished products was 98.5%; and the tensile strength retention rate after 500 hours of thermo-oxidative aging was 92.7%. Compared with Example 1, the replacement of the processing aid slightly optimized the melt flowability and thermo-oxidative stability, while other properties remained basically the same.

[0042] Comparative Example 1 A functional plastic was prepared by the following method: (1) Raw material pretreatment: Commercially available conventional nylon 6 was placed in a vacuum drying oven and dried at 105°C and a vacuum of -0.085MPa for 3.5 hours; lanthanum hypophosphite (purity 99.2%), nano-cerium oxide (particle size 20nm, purity 99.5%), tris(2-hydroxyethyl) isocyanurate (purity 98.5%), and nano-silica (particle size 60nm, after being treated with 4wt% silane coupling agent K) H-560 modified) was dried at 88℃ and vacuum degree -0.085MPa for 7 hours, and the moisture content was 0.15%; caprolactam silane (molecular formula: N-(2-caprolactam ethyl)triethoxysilane, molecular weight 250g / mol, amino content 1.0mmol / g), antioxidant 1010 (purity 99.5%), and calcium stearate (purity 99%) were dried at 80℃ for 2.5 hours to completely remove surface adsorbed water. (2) Premixing: Weigh commercially available conventional nylon 6820g, caprolactam silane 8g, lanthanum hypophosphite 60g, nano cerium oxide 20g, tris(2-hydroxyethyl) isocyanurate 60g, nano silica 20g, antioxidant 1010 6g, and calcium stearate 6g, add them to a 10L high-speed mixer, mix at 1500r / min and 40℃ for 10 minutes, and mix evenly. (3) Melt blending: The premixed material is fed into a twin-screw extruder (length-to-diameter ratio 40:1), and the temperature of each section is set as follows: Zone I 185℃, Zone II 205℃, Zone III 225℃, Zone IV 240℃, Zone V 235℃, and die head 240℃; the screw speed is 265r / min and the feeding speed is 18r / min; after extrusion, it is cooled in a 28℃ water bath, air-dried, and pelletized to obtain flame retardant masterbatch. (4) Molding process: The flame retardant masterbatch was dried at 115℃ and vacuum degree -0.085MPa for 3.5 hours, with a moisture content of 0.09%; it was put into a micro injection molding machine with the following temperatures: Zone I 225℃, Zone II 235℃, Zone III 245℃, Zone IV 250℃, and the die head 245℃; the mold temperature was 50℃, the injection pressure was 90MPa, the holding pressure was 60MPa, the holding time was 15 seconds, and the cooling time was 30 seconds. A standard sample of 3.2mm was obtained by injection molding. (5) Post-treatment: The sample was kept at 82℃ for 2.5 hours and then allowed to cool naturally to eliminate internal stress.

[0043] The product was tested, and the limiting oxygen index (LOI) of this comparative example functional plastic was 32.2%; the vertical flammability rating reached UL94 V-1 (3.2mm specimen), the flameless burning time was 3 seconds, and the flaming drippings ignited absorbent cotton; the tensile strength was 45.5MPa, the elongation at break was 7.6%; and the notched impact strength was 4.1kJ / m. 2 The peak heat release rate (PHRR) is 588.6 kW / m³. 2 Total smoke emissions (TSR) were 2995.8 m³. 2 / m 2TEM testing showed that the rare earth particle size was 840 nm, and the agglomerate content was 14.8%. The processing qualification rate of 1000 finished products was 89.1%. The flame retardant migration was 0.027 mg / kg. After 500 hours of heat aging at 150℃, the tensile strength retention rate was 82.3%. Rare earth in this plastic could not achieve molecular-level dispersion, and agglomeration was serious, resulting in a significant deterioration of various properties.

[0044] Comparative Example 2 A functional plastic was prepared using the method described in Example 1, the only difference being that the polymerization modifier caprolactam-silane was not used. In the in-situ polymerization step, the raw material caprolactam was 828g and the polymerization initiator was 0.166g of deionized water (accounting for 0.02% of the mass of caprolactam monomer).

[0045] The product was tested, and the limiting oxygen index (LOI) of this comparative example functional plastic was 34.6%; the vertical flammability rating reached UL94 V-1 (3.2mm sample), with a flameless burning time of 11 seconds and a easily cracked char layer; the tensile strength was 47.1MPa, the elongation at break was 8.3%; and the notched impact strength was 4.2kJ / m. 2 The peak heat release rate (PHRR) is 496.7 kW / m³. 2 Total smoke emissions (TSR) were 2750.3 m³. 2 / m 2 TEM testing showed that the rare earth particle size was 510 nm, and the agglomerate ratio was 8.2%. The qualified rate of 1000 finished products was 92.3%. After 500 hours of heat aging at 150℃, the tensile strength retention rate was 85.5%. In this plastic, rare earth particles are prone to secondary agglomeration, and the dispersion stability and interfacial bonding are insufficient, resulting in a significant decrease in various properties.

[0046] Comparative Example 3 A functional plastic was prepared by the following method: (1) Raw material pretreatment: caprolactam monomer was placed in a vacuum drying oven and dried at 105°C and vacuum degree -0.085MPa for 3.5 hours. The moisture content was 0.04% by Karl Fischer method. Lanthanum hypophosphite (purity 99.2%) and nano-cerium oxide (particle size 20nm, purity 99.5%) were dried at 88°C and vacuum degree -0.085MPa for 7 hours. The moisture content of both was 0.15%. Caprolactam silane (molecular formula: N-(2-caprolactam ethyl)triethoxysilane, molecular weight 250g / mol, amino content 1.0mmol / g), antioxidant 1010 (purity 99.5%) and calcium stearate (purity 99%) were dried at 80°C for 2.5 hours to completely remove surface adsorbed water. (2) Preparation of rare earth-containing masterbatch by in-situ polymerization: Weigh 900g of caprolactam, 8g of caprolactam-silane, 60g of lanthanum hypophosphite, and 20g of nano-cerium oxide, add them to a 5L polymerization reactor, and then accurately add 0.9g of deionized water (0.1% of the mass of caprolactam monomer) as a polymerization initiator. Replace the initiator with nitrogen three times (1L / min each time, for 5 minutes); start stirring at 350r / min, heat to 150℃ at 5℃ / min, and maintain the temperature for 4.5 hours. The nitrogen gas introduction rate is 0.8L / min; after cooling to room temperature, pelletize to obtain rare earth-containing masterbatch with a particle size of 2.5mm. The viscosity-average molecular weight of the in-situ polymerized nylon 6 is measured to be 3.0×10⁻⁶. 4 (3) Premixing: Weigh 988g of rare earth masterbatch, 6g of antioxidant 1010 and 6g of calcium stearate, add them to a 10L high-speed mixer, mix at 1500r / min and 40℃ for 10 minutes until uniform. (4) Melt blending: Feed the premixed material into a twin-screw extruder (length to diameter ratio 40:1), set the temperature of each section as follows: Zone I 185℃, Zone II 205℃, Zone III 225℃, Zone IV 240℃, Zone V 235℃, and die head 240℃; screw speed 265r / min, feeding speed 18r / min; after extrusion, cool in a 28℃ water bath, air dry, and pelletize to obtain flame retardant masterbatch. (5) Molding process: The flame retardant masterbatch was dried at 115℃ and vacuum degree -0.085MPa for 3.5 hours, with a moisture content of 0.09%; it was put into a micro injection molding machine with the following temperature zones: Zone I 225℃, Zone II 235℃, Zone III 245℃, Zone IV 250℃, and the die head 245℃; the mold temperature was 50℃, the injection pressure was 90MPa, the holding pressure was 60MPa, the holding time was 15 seconds, and the cooling time was 30 seconds. A standard sample of 3.2mm was obtained by injection molding. (6) Post-treatment: The sample was treated at 82℃ for 2.5 hours and then allowed to cool naturally to eliminate internal stress.

[0047] The product was tested, and the comparative example functional plastic showed a limiting oxygen index (LOI) of 33.4%; a vertical flammability rating of UL94 V-1 (3.2mm sample), a flameless burning time of 13 seconds, and a loose and porous char layer; a tensile strength of 48.7 MPa, an elongation at break of 9.2%; and a notched impact strength of 4.7 kJ / m². 2 The peak heat release rate (PHRR) is 476.2.7 kW / m³. 2 Total smoke emissions (TSR) were 2952.9 m³. 2 / m 2 TEM testing showed that the rare earth particle size was 284 nm and the agglomerate ratio was 0.9%; the qualified rate of 1000 finished products was 91.6%; after 500 hours of heat aging at 150℃, the tensile strength retention rate was 85.5%. This plastic has no char-forming reinforcement or physical filling effect, the char layer barrier performance is insufficient, and the flame retardant efficiency and smoke suppression effect are greatly reduced.

[0048] Comparative Example 4 A functional plastic was prepared using the method described in Example 1, the difference being that only lanthanum hypophosphite was used as the rare earth compound, i.e., nano-cerium oxide was replaced with an equal mass of lanthanum hypophosphite.

[0049] The product was tested, and the results showed that the limiting oxygen index (LOI) of this comparative example functional plastic was 35.2%; the vertical flammability rating reached UL94 V-1 (3.2mm specimen), with a flameless burning time of 10 seconds; the tensile strength was 49.3MPa, the elongation at break was 9.6%; and the notched impact strength was 4.9kJ / m². 2 The peak heat release rate (PHRR) is 421.5 kW / m³. 2 The average carbon monoxide yield (YCO) was 0.14 kg / kg; TEM testing showed that the rare earth dispersed particle size was 288 nm, and the agglomerate ratio was 1.1%; the processing qualification rate of 1000 finished products was 93%; it can be seen that the lack of free radical capture function of nano-cerium oxide resulted in insufficient gas phase flame retardancy, poor flame intensity control, and a significant decrease in flame retardancy efficiency.

[0050] Comparative Example 5 A functional plastic is prepared using the method described in Example 1, the difference being that caprolactam-based silane (molecular formula: N-(2-caprolactam-ethyl)triethoxysilane) is replaced with an equal mass of conventional silane coupling agent KH-560.

[0051] The product was tested, and the results showed that the limiting oxygen index (LOI) of this comparative example functional plastic was 36.7%; the vertical flammability rating reached UL94 V-0 (3.2mm specimen), with a flameless burning time of 6 seconds; the tensile strength was 48.9 MPa, the elongation at break was 9.3%; and the notched impact strength was 5.1 kJ / m². 2 The peak heat release rate (PHRR) is 384.2 kW / m³. 2 TEM testing showed that the rare earth particle size was 375 nm, with agglomerates accounting for 3.6%; the pass rate of 1000 finished products was 95%; and the tensile strength retention rate after 500 hours of heat aging at 150℃ was 88.3%. It can be seen that without the use of caprolactam silane, only physical adsorption can improve compatibility, resulting in insufficient dispersion stability and interfacial bonding, and a significant decrease in all properties.

[0052] The above provides a detailed description of a functional plastic and its preparation method. As can be seen from Example 1 and Comparative Example 1, the combined process of in-situ polymerization and melt blending of the present invention is the core innovation to solve the problem of agglomeration in traditional rare earth modified nylon 6. In the in-situ polymerization stage, the nylon 6 molecular chains achieve molecular-level dispersion by encapsulating rare earth particles. Then, the synergistic system distribution is optimized by melt blending, which avoids agglomeration caused by physical mixing from the source, laying the foundation for the synergistic improvement of flame retardancy and mechanical properties.

[0053] As can be seen from Example 1 and Comparative Examples 2 and 5, the dual locking function of caprolactam silane (HLS) is irreplaceable. That is, caprolactam silane (HLS) achieves stable bonding between rare earth particles and nylon 6 matrix through chemical bonding, overcoming the defects of traditional coupling agents such as insufficient dispersion stability and desorption during processing caused by physical adsorption alone, thus ensuring the performance consistency of the material over long-term use.

[0054] As can be seen from Example 1 and Comparative Examples 3-4, the synergistic design of rare earth compound and synergistic system components constructs a complete triple flame retardant mechanism of gas-phase free radical quenching, condensed phase char formation barrier, and physical filling enhancement. The compound of lanthanum hypophosphite and nano-cerium oxide compensates for the shortcomings of gas-phase flame retardancy, while the compound of tris(2-hydroxyethyl) isocyanurate and nano-silica strengthens the barrier effect of condensed phase char layer. The synergy of the two makes the flame retardant efficiency far exceed that of the single system, while also achieving smoke suppression and detoxification functions.

[0055] The preferred embodiments of the present invention have been described in detail above, and are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A functional plastic, characterized in that, It consists of the following components by mass percentage: Plastic matrix 80-85%, core rare earth flame retardant system 6-9%, synergistic flame retardant system 7-10%, polymerization modifier 0.5-1%, processing aid 1-2%; The plastic matrix is ​​in-situ polymerized nylon 6. The core rare earth flame retardant system is composed of lanthanum hypophosphite (LaHP) and nano-cerium oxide (CeO2) in a mass ratio of 3:1, wherein the nano-cerium oxide has a particle size of 2-50 nm. The synergistic flame retardant system is composed of tris(2-hydroxyethyl) isocyanurate and nano-silica in a mass ratio of 3:

1. The polymerization modifier is caprolactam silane (HLS). The processing aid is composed of antioxidant and lubricant in a mass ratio of 1:

1. The antioxidant is antioxidant 1010 or antioxidant 1076, and the lubricant is calcium stearate or pentaerythritol stearate (PETS).

2. The functional plastic according to claim 1, characterized in that, The mass percentages of each component are as follows: in-situ polymerized nylon 682%, lanthanum hypophosphite 6%, nano cerium oxide 2%, tris(2-hydroxyethyl) isocyanurate 6%, nano silica 2%, caprolactam silane 0.8%, antioxidant 1010 0.6%, and calcium stearate 0.6%.

3. The functional plastic according to claim 1, characterized in that, The viscosity-average molecular weight of in-situ polymerized nylon 6 is 3.0 × 10⁻⁶. 4 -5×10 5 .

4. The functional plastic according to claim 1, characterized in that, The caprolactam-silane has a molecular weight of 200-300 g / mol and an amino content of 0.8-1.5 mmol / g.

5. The functional plastic according to claim 1, characterized in that, The nano-silica is surface modified with silane coupling agent KH-560, and the amount of the modifier is 3-5% of the mass of the nano-silica.

6. The functional plastic according to claim 1, characterized in that, The plastic matrix can be replaced with in-situ polymerized nylon 6 / polyamide 66 at a mass ratio of 9:

1.

7. A method for preparing the functional plastic according to claim 1, characterized in that, Includes the following steps: (1) Raw material pretreatment: Vacuum dry caprolactam monomer at 100-110℃ for 3-4 hours, and control the moisture content below 0.05%; Vacuum dry lanthanum hypophosphite, nano cerium oxide, tris(2-hydroxyethyl) isocyanurate, and nano silica at 85-90℃ for 6-8 hours, and control the moisture content below 0.2%; Dry caprolactam silane and processing aids at 80℃ for 2-3 hours to remove surface adsorbed water; (2) Preparation of rare earth-containing masterbatch by in-situ polymerization: Weigh the pretreated caprolactam monomer, caprolactam silane, lanthanum hypophosphite and nano-cerium oxide according to the mass percentage, add them to the polymerization reactor, and then add 0.02%-0.5% of deionized water as a polymerization initiator to the reactor. Nitrogen gas was introduced for protection, and the temperature was raised to 145-155℃. The stirring rate was 300-400 r / min, and the polymerization was maintained at this temperature for 4-5 hours. After the polymerization was completed, the heating was stopped, and the mixture was continuously stirred and cooled to room temperature. The material was then discharged and pelletized to obtain in-situ polymerized nylon 6 masterbatch containing rare earth elements. (3) Premixing: Weigh out the rare earth-containing in-situ polymerized nylon 6 masterbatch, tris(2-hydroxyethyl) isocyanurate, nano silica and processing aids by mass percentage, add them to a high-speed mixer, mix at 1300-1600 r / min for 8-12 minutes, and control the mixing temperature at 35-45℃ to obtain a uniform premix. (4) Melt blending: The premixed material is fed into a twin-screw extruder, melt blended and extruded, cooled in a water tank and air-dried, and then pelletized by a pelletizer to obtain flame retardant masterbatch; (5) Molding and processing: The flame retardant masterbatch is vacuum dried at 110-120℃ for 3-4 hours, and then injected into a micro injection molding machine to produce finished plastic packaging materials; (6) Post-treatment: The molded finished product is kept at 80-85℃ for 2-3 hours to eliminate internal stress.

8. The method for preparing the functional plastic according to claim 7, characterized in that, In step (2), the stirring rate of the polymerization reactor is 350 r / min, the polymerization temperature is 150℃, the holding time is 4.5 hours, and the nitrogen gas introduction rate is 0.5-1 L / min; in step (4), the length-to-diameter ratio of the twin-screw extruder is 40:

1.

9. The method for preparing the functional plastic according to claim 7, characterized in that, In step (4), the temperature of each section of the twin-screw extruder is set as follows: Zone I 180-190℃, Zone II 200-210℃, Zone III 220-230℃, Zone IV 235-245℃, Zone V 230-240℃, and the die head temperature is 235-245℃; the screw speed is 250-280r / min, and the feeding speed is 17-20r / min; In step (5), the temperature of each section of the injection molding machine is set as follows: Zone I 220-230℃, Zone II 230-240℃, Zone III 240-250℃, Zone IV 245-255℃, and the die head temperature is 240-250℃; the injection pressure is 80-100MPa, the holding pressure is 50-70MPa, the holding time is 12-20 seconds, the cooling time is 25-35 seconds, and the mold temperature is 45-60℃.

10. The method for preparing the functional plastic according to claim 9, characterized in that, In step (5), the temperature of the injection mold is 50°C and the cooling time is 30 seconds.

Citation Information

Patent Citations

  • Rare earth-containing phosphite as well as preparation method, application and composition thereof

    CN118978134A

  • Composite flame retardant, flame-retardant ABS (Acrylonitrile Butadiene Styrene) composition and preparation method and application thereof

    CN120248436A

  • High-performance polyamide flame-retardant composite material based on element synergistic effect and preparation method thereof

    CN120904679A